Impact of Vehicle Distance Traveled on Motor Oil Properties - Alaeddin Ejledi; Suliman Hensheri (AlQalam Journal of Medical and Applied Sciences, 2024)
This comprehensive study delved into the impact of vehicle distance traveled and engine operating periods on motor oil properties, specifically focusing on viscosity and foaming characteristics. The findings unveiled a pivotal juncture in motor oil performance, with discernible viscosity degradation emerging after 10,000 kilometers, most notably within the 10,000-to-12,000-kilometer range. The study also shed light on foaming tendencies within the oil, indicating potential heightened friction and engine stress, particularly as mileage increased. The research underscores the critical need to incorporate these real- world driving factors into maintenance and oil change decisions, offering the prospect of fine-tuning engine performance and extending the longevity of engines. The practical implications of these insights are substantial, empowering vehicle operators to make more informed decisions regarding motor oil choices and suggesting the potential for formulating specialized motor oils capable of withstanding a wide spectrum of driving conditions. These findings carry broad-reaching implications for vehicle owners, manufacturers. and the automotive industry as a whole, aiming to enhance both performance and sustainability in the realm of internal combustion engines. هذه الدراسة تناولت تأثير المسافة المقطوعة بواسطة المركبة وفترات تشغيل المحرك على خصائص زيت المحرك، مع التركيز بشكل خاص على اللزوجة وخصائص الرغوة. أظهرت النتائج نقطة تحول حاسمة في أداء زيت المحرك، حيث لوحظ تدهور ملحوظ في اللزوجة بعد 10,000 كيلومتر، وخاصة في النطاق من 10,000 إلى 12,000 كيلومتر. كما تسلط الدراسة الضوء على ميل الرغوة في الزيت، مما يشير إلى زيادة محتملة في الاحتكاك وإجهاد المحرك، وخاصة مع زيادة المسافة المقطوعة. ناقشت الدراسة أهمية تضمين هذه العوامل الواقعية في قرارات الصيانة وتغيير الزيت، مما يقدم فرصة لتعديل أداء المحرك وإطالة عمره. إن الآثار العملية لهذه النتائج كبيرة، إذ تمكن مشغلي المركبات من اتخاذ قرارات أكثر استنارة بشأن اختيارات زيت المحرك، وتقترح إمكانية صياغة زيوت محرك متخصصة قادرة على تحمل مجموعة واسعة من ظروف القيادة. تحمل هذه النتائج آثاراً واسعة النطاق لمالكي المركبات، والمصنعين، وصناعة السيارات بشكل عام، وتهدف إلى تعزيز الأداء والاستدامة في عالم محركات الاحتراق الداخلي